THE EFFECT OF USING CALCIUM SOAP IN THE RATION ON THE PERFORMANCE OF MALE BALI DUCKS - A.A.A.A.S., Suamba; Bidura, I G.N.G; Candrawati, D.P.M.A. (Jurnal Peternakan Tropika; Vol 10 No 2 (2022): Vol. 10 No. 2 Tahun 2022; May - August, 2022)
This study aims to determine the effect of the use of calcium soap in the ration on the performance of male bali ducks.  The research was carried out for 42 days at Jalan Tegal Wangi II Gang Kavling No.  9 Sesetan, Denpasar, Bali.  The design used was a completely randomized design (CRD) consisting of 4 treatments and 6 replications.  Each experimental plot was filled with 4 male bali ducks for 14 days with  an average body weight of 178 g ± 20.8. The four treatments were male bali ducks fed rations without calcium soap as control (A), rations with 1% calcium soap (B), rations with 2% calcium soap (C), and rations with 3% (D).  The variables observed were initial body weight, ration consumption, final body weight, weight gain, and Feed Conversion Ratio (FCR).  The consumption of male bali ducks rations that received treatment B, C, and D was statistically significantly lower (P<0.05) compared to treatment A.  Final body weight and weight gain were statistically significantly higher (P<0.05) higher from treatment A.  Feed conversion ratio of treatment B, C, and D was statistically significantly lower (P<0.05) lower than treatment A.  From the results of the study, it can be concluded that giving calcium soap to male bali ducks aged 2-8 weeks can reduce ration consumption, increase final body weight and weight gain and the Feed Conversion Ratio is more efficient.   Keywords: Male Bali Duck, Performance, Calcium soap